Substrate-Independent Design of Liquid-Infused Slippery Surfaces via Mussel-Inspired Chemistry - Chiera, Salvatore; Bittner, Carina; Vogel, Nicolas (Advanced Materials Interfaces, 2021)
Self-cleaning and repellent coatings ensure enduring performance of surfaces in many areas of technology and everyday life. An ideal repellent coating is efficient in removing contaminations, yet easy to apply on a wide range of surface materials. To devise such a coating, two bioinspirations are combined that show opposing interfacial properties: the peristome of a pitcher plant and the versatile mussel-inspired chemistry of polydopamine (PDA). The possibility of PDA to bind to different surface materials is taken to provide a material-independent coating strategy. Its reactivity toward amines to cofunctionalize the coating with monoaminopropyl-polydimethylsiloxane is utilized to control the surface chemistry. This process, in effect, adheres silicone polymer chains to any desired surface material. Finally, inert silicone oil is added to the reaction mixture to provide in situ lubrication of the coating. Together, the process creates lubricant-infused surfaces in a one-step process independent of the underlying substrate. It is shown that the reaction mixture can be deposited by dip or spray coating, providing procedures to coat large surfaces and complex samples such as textiles and wood. The combination of the mussel-inspired chemistry with the pitcher plant-inspired control of wettability provides an experimentally simple coating process to impart efficient repellency and self-cleaning characteristics to virtually any surface material.
CRIS-Team Scopus Importer:2021-05-14
Keywords: liquid infused surfaces; liquid repellency; mussel-inspired chemistry; polydopamine; slippery surfaces; spray coating